2022
DOI: 10.1038/s41467-022-27953-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific multi-omics analysis of atrial fibrillation

Abstract: Genome-wide association studies (GWAS) for atrial fibrillation (AF) have uncovered numerous disease-associated variants. Their underlying molecular mechanisms, especially consequences for mRNA and protein expression remain largely elusive. Thus, refined multi-omics approaches are needed for deciphering the underlying molecular networks. Here, we integrate genomics, transcriptomics, and proteomics of human atrial tissue in a cross-sectional study to identify widespread effects of genetic variants on both transc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 91 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…Due to the cis effect of single nucleotide polymorphism (SNP) alleles on transcription and translation gene expression quantitative trait loci (eQTL), some eQTL are disease-context dependent, observable only under speci c physiological conditions, e.g., unique stress or stimulus. eQTL shows a high degree of tissue speci city [8][9][10] , emphasizing the need to examine disease organ tissue. Therefore, we studied patients experiencing myocardial ischemia while undergoing cardiac surgery with cardiopulmonary bypass (CPB).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the cis effect of single nucleotide polymorphism (SNP) alleles on transcription and translation gene expression quantitative trait loci (eQTL), some eQTL are disease-context dependent, observable only under speci c physiological conditions, e.g., unique stress or stimulus. eQTL shows a high degree of tissue speci city [8][9][10] , emphasizing the need to examine disease organ tissue. Therefore, we studied patients experiencing myocardial ischemia while undergoing cardiac surgery with cardiopulmonary bypass (CPB).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26]28,29 Specifically, AF multiomic analysis on atrial tissues has provided novel into the molecular pathways implicated in the pathology. 4,32,50,51 However, the need of cardiac biopsies, has limited enthusiasm of this technology to a small subpopulation of AF including those with valvular heart disease or CHD, for whom surgical intervention is already warranted. To overcome this, a surrogate tissue source is warranted to provide an indirect epigenetic and/or transcriptional phenotyping to mirror the failing myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…A mounting body of evidence supports a future for ‘clinical epigenetics’ in cardiovascular medicine 22–26,28,29 . Specifically, AF multiomic analysis on atrial tissues has provided novel insights into the molecular pathways implicated in the pathology 4,32,50,51 . However, the need of cardiac biopsies, has limited enthusiasm of this technology to a small subpopulation of AF patients including those with valvular heart disease or CHD, for whom surgical intervention is already warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, which specific cell type is contributing to the production of these secretory proteins is unclear. In addition, by examining the relationship between pQTLs and eQTLs, previous studies have demonstrated the disparity of genetic variants associated with mRNA expressions and protein abundances as summarized by a minireview ( 7 ), and a recently published study affirms this observation with substantial difference between pQTLs and eQTLs where only 32% of the index eQTLs variants were replicated in pQTLs ( 8 ). While previous studies examining the extent of overlap between pQTLs and eQTLs extensively explored steady-state conditions, the degree to which these findings are replicated in stimulated conditions remain elusive.…”
Section: Introductionmentioning
confidence: 92%